Influence of delivery and feeding mode in oral fungi colonization – a systematic review - Maria Joao Azevedo; Maria de Lurdes Pereira; Ricardo Araujo; Carla Ramalho; Egija Zaura; Benedita Sampaio-Maia (Microbial Cell)
Postnatal acquisition of microorganisms from maternal and environmental sources contributes to the child microbiome development. Several studies showed that the mode of delivery and breastfeeding may have impact on the oral bacterial colonization, however, the influence on oral fungal colonization is still unknown. We performed a systematic literature review on mother to child oral fungi transmission, namely regarding the association between the mode of delivery and breastfeeding in oral yeast colonization. Our analysis revealed no significant differences between the oral mycobiome of breastfed and bottle-fed children. As for the delivery mode, the majority of studies found a relation between fungal colonization and vaginal delivery. Candida albicans was the most commonly isolated fungi species. Our analysis suggests that maternal breastfeeding does not seem to influence oral mycology, but vaginal delivery appears to promote oral yeast colonization in early life.